Differences among epitopes recognized by neutralizing antibodies induced by SARS-CoV-2 infection or COVID-19 vaccination - Yamamoto, S; Yamayoshi, S; Ito, M; Sakai-Tagawa, Y; Nakachi, I; Baba, R; Kamimoto, S; Ogura, T; Hagiwara, S; Kato, H; Nakajima, H; Uwamino, Y; et al. (Cell Press, 2023)
SARS-CoV-2 has gradually acquired amino acid substitutions in its S protein that reduce the potency of neutralizing antibodies, leading to decreased vaccine efficacy. Here, we attempted to obtain mutant viruses by passaging SARS-CoV-2 in the presence of plasma samples from convalescent patients or vaccinees to determine which amino acid substitutions affect the antigenicity of SARS-CoV-2. Several amino acid substitutions in the S2 region, as well as the N-terminal domain (NTD) and receptor-binding domain (RBD), affected the neutralization potency of plasma samples collected from vaccinees, indicating that amino acid substitutions in the S2 region as well as those in the NTD and RBD affect neutralization by vaccine-induced antibodies. Furthermore, the neutralizing potency of vaccinee plasma samples against mutant viruses we obtained or circulating viruses differed among individuals. These findings suggest that genetic backgrounds of vaccinees influence the recognition of neutralizing epitopes.